Context-Dependent IL-1 mRNA-Destabilization by TTP Prevents Dysregulation of Immune Homeostasis Under Steady State Conditions - Sneezum, Lucy; Eislmayr, Kevin; Dworak, Helene; Sedlyarov, Vitaly; Le Heron, Anita; Ebner, Florian; Fischer, Irmgard; Iwakura, Yoichiro; Kovarik, Pavel (Frontiers in Immunology, 2020)
The bioavailability of the major pro-inflammatory cytokines IL-1α and IL-1β is tightly controlled by transcription and post-translational processing to prevent hyperinflammation. The role of mRNA decay in maintenance of physiological IL-1 amounts remained unknown. Here we show that the down-regulation of Il1a and Il1b mRNA by the mRNA-destabilizing protein TTP (gene Zfp36) is required for immune homeostasis. The TTP deficiency syndrome, a multi organ inflammation in TTP-/- mice, was significantly ameliorated upon deletion of the IL-1 receptor. Il1a and Il1b played non-redundant roles in triggering the pathological IL-1 signaling in TTP-/- mice. Accordingly, tissues from TTP-/- animals contained increased amounts of Il1b mRNA. Unexpectedly, TTP destabilized Il1b mRNA in cell type-specific ways as evident from RNA-Seq and mRNA stability assays. These results demonstrate that TTP-driven mRNA destabilization depends on the cellular context. Moreover, such context-defined mRNA decay is essential for keeping steady state IL-1 levels in the physiological range.